Shisha tobacco component composition - N. N. Matyukhina; A. G. Mirgorodskaya; M. V. Shkidyuk; O. K. Bedritskaya (Новые технологии, 2019)
Shisha tobacco is a type of smoking tobacco product intended for smoking using a hookah and representing a mixture of cut or torn raw materials for the production of tobacco products with or without non-tobacco raw materials and other ingredients. The specificity of the consumption of this type of tobacco product is production of highly dispersed aerosol as a distillation product, the physiological strength of which is determined by the nicotine content in the hookah mixture. Systemic research of the "Tobacco for hookah" product, of its component composition and chemical composition of the aerosol produced has not been carried out. There are no standards for the content of toxic aerosol components for this product category. The selection of the component composition of the hookah mixture, taking into account the cost of the final product and its toxic load, is a modern technological method for modeling the ingredient composition, which is based on tobacco raw materials". Methods commonly used in tobacco industry and the following equipment was used to conduct the research: CERULEAN SM 405 linear smoking machine; Thermo Scientific Dionex UltiMate 3000 liquid chromatograph and TSQ Quantiva mass spectrometer using high performance LC-MS / MS liquid chromatography / mass spectrometry; Crystal 2000M Chromatograph; CO analyzer, Magix Shisha Since hookah. The article presents the results of studies to determine the content of nicotine and carbon monoxide in an aerosol produced by industrial and experimental tobacco samples for hookah, depending on the use of various tobacco raw materials and tobacco fines. As a result of the research, methods have been developed for collecting aerosol and determining the content of conditionally toxic compounds (acetaldehyde, formaldehyde, acrolein) in an aerosol produced by hookah mixtures, for an objective assessment of a tobacco product safety level.